Case Report: Integrative naturopathic approach for the management of sequestered lumbar disc herniation with neurological impairments: a case series with two year follow up - Paudel, Sunil; Paudel, Chethana A. M.; Silwal, Karishma (Frontiers in Pain Research, 2024)
Lumbar Disc Herniation (LDH) is a common condition, and contemporary pain research emphasizes the importance of adopting a comprehensive biopsychosocial perspective in pain treatment for positive clinical outcomes. Integrated Naturopathy and Yoga (INY) is a non-invasive medical system that takes a holistic and patient-centric approach to healing diseases. However, there is limited evidence on the effectiveness of INY, particularly in managing Sequestered LDH. We present two cases of patients experiencing radicular low back pain, lower limb weakness, and neuro-claudication who opted for conservative naturopathic management with INY. Following the INY treatments, both patients reported gradual relief from lower back pain, radicular pain, and neurological deficits. These findings are significant and contribute valuable evidence, suggesting that INY could be a viable therapeutic approach for managing sequestered LDH. This represents the first report on a non-invasive method for resolving sequestered LDH by utilizing INY.